MICA ∗012:01 Allele Facilitates the Metastasis of KRAS-Mutant Colorectal Cancer - Ding, Weifeng; Ma, Yanyun; Zhu, Weifeng; Pu, Weilin; Zhang, Jianfeng; Qian, Fei; Zhou, Youlang; Deng, Yan; Guo, Shicheng; Wang, Jiucun; Zhou, Xiaodong (Frontiers in Genetics, 2020)
Major histocompatibility complex (HLA) class I chain-related protein A (MICA) regulates immune surveillance through activation of NKG2D (natural killer group 2D) receptor. However, the genetic association, potential function, and predictive ability of MICA alleles with colorectal cancer (CRC) prognosis remain undefined. In this study, we characterized MICA alleles in tissue samples from 104 patients with CRC and 536 healthy controls and carried out genetic association studies by molecular and clinical CRC phenotypes. Preliminary sequence analysis revealed that MICA *009:01 or *049 alleles were significantly decreased in patients with CRC (p=0.0049), and further stratification analysis indicated that MICA *012:01 allele was associated with patients with CRC and carrying KRAS codon 12 mutation (p=0.027). The functional consequences of MICA alleles were examined via transfected CRC cell lines which showed that overexpression of MICA *012:01 enhanced the proliferation, invasion, and metastatic phenotype of CRC. Preliminary analysis of disease-free survival time in patients with and without MICA *012:01 suggest this allele may be predictive for poor prognosis of patients with KRAS codon 12 mutated CRC, as no somatic mutation of MICA gene was detected in CRC tumors compared to paracancerous tissues. Our study indicates that MICA *012:01 allele is associated with KRAS-mutated CRC, facilitates CRC invasion and metastasis, and possibly reduces the survival of patients with KRAS-mutated CRC.